Jaringan Distribusi dan Relasi Pasar Petani Kubis di Dataran Tinggi Ijen - Zulfa, Qorina; Yuswadi, Hary (Jurnal ENTITAS SOSIOLOGI, 2021)
The study entitled "Distribution Network and Market Relations of Cabbage Farmers in the Ijen Plateau" was motivated by Ijen farmers as the largest producer of cabbage vegetable commodity in the Horseshoe area (Jember, Lumajang, Probolinggo, Situbondo, Bondowoso). Lack of market access, market information, and capital make it difficult for farmers to increase income. Access or distance from the city center or market also influences the difficulty of Ijen highland farmers to interact and relate with market actors. As a result, farmers are reluctant to connect and choose their marketing channel with the selling system to Traders who come before the harvest. It causes some farmers to experience dependence and passivity in attempting to maintain relations with market actors, even though in this felling system, as much as 40% of the farmers' harvest sales results become the property of Traders. The method used in this research is the descriptive qualitative method, using purposive informant retrieval techniques. Data collection techniques using observation, in-depth interviews, documentation, and literature study. Data validity test uses data triangulation. Overview of social capital theory from Puntu (1993) and rational choice theory from Jame S Coleman (1990). The results obtained from this study are that farmers can have a superior economic position if they have good marketing relations and are willing to sacrifice time and energy, and have sufficient funds for distribution. Hence, farmers have the opportunity to establish relationships with market actors so that they will get more profits. Keywords : Cabbage farmers, market relations, distribution Penelitian dengan judul “Jaringan Distribusi dan Relasi Pasar Petani Kubis di Dataran Tinggi Ijen” dilatarbelakangi oleh petani Ijen sebagai penghasil komoditi sayur kubis terbesar pada wilayah Tapal Kuda. Kurangnya akses pasar, informasi pasar dan modal membuat petani sulit meningkatkan penghasilan. Akses atau jarak tempuh yang jauh dari pusat kota atau pasar turut mempengaruhi kesulitan petani dataran tinggi Ijen untuk berinteraksi dan berelasi dengan aktor pasar. Akibatnya petani enggan berelasi dan memilih jalur pemasaran sendiri dengan sistem tebang jual kepada pedagang yang datang menjelang masa panen. Hal ini menyebabkan sebagian petani mengalami ketergantungan dan pasif dalam bersikap mengusahakan relasi dengan aktor pasar, padahal pada sistem tebang jual ini sebanyak 40% hasil penjualan panen petani menjadi hak milik pedagang. Metode yang digunakan dalam penelitian ini adalah metode kualitatif deskriptif, dengan menggunakan teknik pengambilan informan purposive. Teknik pengumpulan data menggunakan observasi, wawancara mendalam, dokumentasi, dan studi kepustakaan. Uji keabsahan data menggunakan Triangulasi data. Tinjauan teori modal sosial dari Puntu (1993), dan teori pilihan rasional dari Jame S Coleman (1990) dijadikan acuan dalam penelitian ini. Hasil yang diperoleh dari penelitian ini adalah petani dapat memiliki posisi perekonomian yang unggul apabila memiliki relasi pemasaran yang baik serta bersedia untuk berkorban waktu dan tenaga, juga memiliki dana yang cukup untuk distribusi, maka petani memiliki peluang untuk dapat menjalin relasi dengan aktor pasar, sehingga keuntungan yang didapatkan akan lebih banyak. Kata kunci : Petani kubis, relasi pasar, distribusi.